Application of Learning Model Auditory, Intellectually, Repetition (Air) to Increase Student Activity and Learning Outcomes in 2013 Curriculum Integrated Thematic Learning in Class IV SDN 06 Hand of Padang - Leni Elisa; Hadiyanto Hadiyanto; Yanti Fitria (International Journal of Educational Dynamics, 2019)
This study aims to improve the activities and learning outcomes of students in class 06 Tangah Padang uses the Learning Model Auditory, Intellectually, Repetition (Air) This research is a classroom action research. The instruments used in this study are observation sheets and test results. This study consisted of two cycles with a total of 22 students. Each cycle consists of the stages of planning, action, observation, and reflection. Student activity is said to increase if it has achieved a success indicator of ≥ 50% and learning outcomes increase if it reaches the success indicator ≥ 70% after being applied to the Learning Model Auditory, Intellectually, Repetition (Air). The results of the study indicate an increase in the activities and student learning outcomes. Student activities in the first cycle were 42.85% and the second cycle was 78.57%. Learning outcomes in the first cycle were 47.61% and the second cycle was 80.95%. Based on the results of the study that the Learning Model Auditory, Intellectually, Repetition (Air) can be used as an alternative in the learning process. Keywords: WATER Model, Activities, Learning Outcomes, Integrated Learning